Chemical Space for Peptide-based Antimicrobials - Markus Orsi; Hippolyte Personne; Etienne Bonvin; Thierry Paschoud; Basak Olcay; Xiaoling Hu; Sacha Javor; Jean-Louis Reymond (CHIMIA)
Multidrug-resistant (MDR) bacteria represent a global public health threat, and antimicrobial peptides (AMPs), derived from naturally occurring linear or cyclic peptides, can provide the solution. However, most AMPs are sensitive to proteases and have poor pharmacokinetics. The EU-funded ERC Advanced Grant SPACE4AMPS aims to identify new AMPs by applying the concepts of chemical space and ligand-based virtual screening, which are well known for small molecule drug discovery, to the world of peptides. We create virtual libraries of peptides and related molecules and use these approaches to select a few tens of compounds for synthesis and detailed. evaluation of antibacterial, toxicity and stability effects. Recent results and prospects of this ongoing project are presented in this review.